High-performance electrically conductive adhesives with aluminum-doped zinc oxide (AZO) for various flexible electronic devices. (5th December 2022) - Cai, Shaoyong; Cao, Ge; Chen, Yonghao; Zhang, He; Jiang, Chengwei; Tian, Yanqing
Graphical abstract: Highlights: Development of high-performance and low-cost ECAs system. The addition of AZO nanoparticles could significantly enhance the conductivity of ECAs. The fabricated flexible electronic devices worked reliably under extreme conditions. Abstract: Electrically conductive adhesives (ECAs) are a kind of attractive alternative to tin solders in microelectronics. However, fabricating high-performance, low-cost ECAs remains challenging due to the need for high-content metal fillers. This work reported a facile preparation of cost-effective ECAs composed of aluminum-doped zinc oxide (AZO) nanoparticles and silver (Ag) micro-flakes. The AZO nanoparticles could serve as a "bridge" to connect neighboring Ag micro-flakes to significantly improve the ECAs′ conductivity (from 1638.8 × 10 -5 Ω⋅cm to 8.5 × 10 -5 Ω⋅cm). After the aging and bonding performance tests, prototyped applications of the as-prepared ECAs for three flexible electronic devices were demonstrated sequentially: (Ⅰ) The resistance of flexible conductive film showed excellent dynamic stability after being folded for 1000 cycles, bent/released within 6 mm radius for more than 2000 cycles, or applied with 1000 kPa pressure; (Ⅱ) The coil antenna achieved fast transmission of radio frequency signal for near field communication (NFC) system; (III) The flexible heater performed efficient thermal management at 0.4–1.4 V input voltages. Therefore, the fabricated ECAs are expected to provide new opportunities for the development of novel flexible electronic devices for future applications.